Pengaruh Religiusitas Machiavellian dan Love Money terhadap Penggelapan Pajak - Reski Lestari; Junaidi Junaidi; I Ketut Patra (Owner : Riset dan Jurnal Akuntansi, 2023)
Today, most of countries depend on the tax income. Tax income play important role to fund the government expenditure. On the other hand, the tax is a main source of governemtn income. It common, especially among developing countries such as Indonesa. However, some cases of tax evasion among tax-payers need to uncover which factors to influence tax-payers attitude and behavior. Most of Indonesia’ people daily life refers to their religion, hence religion has crucial role to influence their actions and views. This study also examines the relationship between religion and love of money among tax-payers who thinking on tax evasion. This study aims to determine the effectst of religiosity on Machiavellian. FurthermoreMoreover, the recent study also investigates the role of love of money on tax evasion. It provides best insight to staholders who care on tax income. The population avoided in this study is the taxpayers of Luwu Raya, and the data collected viw online survey through Google Form. This study used a questionnaire instrument with as many as 334 respondents. Structural Eqution Modelling (SEM) was used to examine research hyphotheses. The results showed that religiosity does not jave crucial effect on tax payers love of money. Meanwhile, Religiosity has positive and significant effect on Machiavellian and love of money. Furthermore, love of money also has positicei effect on tax evasion.